Plasmodium falciparum rosetting is associated with malaria severity in Kenya. - Rowe, A; Obeiro, J; Newbold, C; Marsh, K (1995)
Rosette formation in 154 fresh Plasmodium falciparum isolates from Kenyan children with mild (n = 54), moderate (n = 64), or severe (n = 36) malaria was studied to determine whether the ability to form rosettes in vitro is correlated with malaria severity. There was a wide distribution of rosette frequencies within each clinical category; however, a clear trend towards higher rosette frequency with increasing severity of disease was seen, with the median rosette frequency of the mild-malaria group (1%; range, 0 to 82%) being significantly lower than those of the moderate-malaria group (5%; range, 0 to 45%; Mann-Whitney U test, P < 0.02) and the severe-malaria group (7%; range, 0 to 97%; Mann-Whitney U test, P < 0.003). Within the severe-malaria category there was no difference in rosetting among isolates from cerebral malaria patients or those with other forms of severe malaria. We also examined the ABO blood groups of the patients from whom isolates were obtained and found that isolates from group O patients (median rosette frequency, 2%; range 0 to 45%) rosetted less well than those from group A (median, 7%; range 0 to 82%; Mann-Whitney U test, P < 0.01) or group AB (median, 11%; range 0 to 94%; Mann-Whitney U test, P < 0.03). We therefore confirm that rosetting is associated with severe malaria and provide further evidence that rosetting is influenced by ABO blood group type. Whether rosetting itself plays a direct role in the pathogenesis of severe malaria or is a marker for some other causal factor remains unknown.